Validity and reliability of cognitive tests study and development of elementary curriculum using Rasch model - Muhammad Erfan; Mohammad Archi Maulyda; Ida Ermiana; Vivi Rachmatul Hidayati; Arif Widodo (Research and Social Study Institute, 2020)
The instrument for measuring knowledge in the subject of Elementary School Curriculum Study and Development has been created to measure students' understanding of teacher candidates in applying concepts, implications and curriculum development at the elementary school level. In order to make reliable and feasible instrument for measuring students knowledge in the subject of Elementary School Curriculum Study and Development, this study aims to produce empirical evidence about the validity and reliability of test instruments using the Rasch model analysis. The study was conducted by testing 20 items on 142 elementary school teacher candidate at one of the State Universities in the City of Mataram, West Nusa Tenggara. The validity and reliability of the instrument were measured by the Rasch analysis model using the Winstep program. The one-dimensional testing of 20 items has a variance measured at 42.7% which exceeds the minimum points of 40.0% desired by the Rasch model. The reliability index of the respondents was 0.65 and the item reliability index was 0.98. All items show a positive value for Point Measure Correlation (PMC) in terms of item polarity which means there is no conflict between the item and the construct being measured. Outfit Mean Square value also shows that all items that almost all items have an MNSQ Outfit value smaller than 1.5 which means the measurement value can be said to be productive except for item 13 (3.77) and item 16 (3.77). Both of these items need to be re-examined because they have problems in measuring their validity. The results of this study have proven that the knowledge measurement test instrument in the Elementary School Curriculum Study and Development course has validity and reliability values that meet and are empirically feasible to be used in measuring Basic School Curriculum Study and Development knowledge for prospective teacher students.